Thrombin Alters Human Endometrial Stromal Cell Differentiation During Decidualization - Babayev, Samir N. (Reprod Sci, 2018)
Vaginal bleeding and subchorionic hematomas are associated with increased risk of both early and late pregnancy loss. Thrombin generation may play a pivotal role in the development of these complications. To determine the effects of thrombin on human endometrial stromal cells (hESCs), cells were treated with thrombin at baseline or during decidualization with cyclic adenosine monophosphate (cAMP)+medroxyprogesterone acetate (MPA). Next-generation RNA sequencing revealed that markers of decidualization (IGF-1, IGFBP-1, and prolactin [PRL]) were induced after the initiation of decidualization, whereas thrombin suppressed insulin-like growth factor (IGF)-1, Insulin-like growth factor binding protein (IGFBP)-1, and PRL gene expression at baseline and during decidualization. These effects were mediated through protease activated receptor (PAR)-1- and PAR-1-independent pathways. Thrombin decreased the secretion of a key marker of decidualization (PRL), altered the morphological transformation of decidualizing hESCs, and activated genes involved in matrix degradation and proinflammatory chemokines (Interleukin-8 and Interleukin-6). Genes encoding factors important for matrix stability (Col1α1, LOX) were suppressed. We suggest that intrauterine bleeding and generation of thrombin accentuates leukocyte extravasation and endometrial inflammation, impairs decidualization, and endometrial support of early pregnancy.